Train to Pakistan - Khushwant Singh (Karachi Oxford, 1998)
It is a place, [the author] tell[s] us at the beginning of this classic novel, where Sikhs and Muslims have lived together in peace for hundreds of years. Then one day, at the end of the summer, the "ghost train" arrives, a silent, incredible funeral train loaded with the bodies of thousands of refugees, bringing the village its first taste of the horrors of the civil war. [This] is the story of this isolated village that is plunged into the abyss of religious hate. It is also the story of a Sikh boy and a Muslim girl whose love endures and transcends the ravages of war.-Back cover.
Keywords: India--Punjab -- Partition of Punjab (India : 1947)